1998
DOI: 10.1143/jjap.37.l1283
|View full text |Cite
|
Sign up to set email alerts
|

New Semiconductor Alloy GaAs1-xBix Grown by Metal Organic Vapor Phase Epitaxy

Abstract: A new semiconductor alloy material, GaAs1-x Bi x has been created by Metal Organic Vapor Phase Epitaxial (MOVPE) growth. A low growth temperature, such as 365°C, is required to obtain the alloy. X-ray diffraction measurements of alloy layers reveal that the diffraction patterns are satisfactory. The maximum GaBi content in the GaAsBi alloy estimated from the lattice constant is around 2%, which is consistent with that estimated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(135 citation statements)
references
References 5 publications
8
127
0
Order By: Relevance
“…By performing temperature-dependent PL [164], Oe and Okamoto reported that the thermally induced bandgap redshift in GaAsBi is much less sensitive than that in GaAs [32]. Yoshida et al obtained the same results with PR measurements later [48].…”
Section: Optical Bandgapmentioning
confidence: 77%
See 2 more Smart Citations
“…By performing temperature-dependent PL [164], Oe and Okamoto reported that the thermally induced bandgap redshift in GaAsBi is much less sensitive than that in GaAs [32]. Yoshida et al obtained the same results with PR measurements later [48].…”
Section: Optical Bandgapmentioning
confidence: 77%
“…When both N and Bi are used, it is possible to independently control CB and VB in GaAsNBi, and thus extend light emission wavelength very efficiently. Other beneficial properties when using Bi include large spin-orbit (SO) split band [46,47], less temperature sensitive bandgap [32,48,49], minor influence on both electron [50] and hole mobility [51] for small Bi concentrations, enhancement of PL intensity [44] and surfactant effect ensuring smooth surface [52], etc. Sweeney and Jin proposed theoretically that GaAsNBi is promising for efficient near IR light emitting devices [53].…”
Section: Theoretical Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloying of gallium arsenide (GaAs) with bismuth (Bi) efficiently reduces the band gap E g and enhances the spinorbit splitting [1][2][3] , the magnitude of which exceeds the energy gap (E g ) of GaAs 1−x Bi x at the Bi content of x Bi 9% 4 . Sweeney et al 5 suggested that these properties can lead to a suppression of non-radiative losses in GaAs 1−x Bi x alloys (bismides) by creating off-resonance conditions for the Auger recombination 6 , thus making dilute bismide semiconductors a promising candidate for GaAs-based lasers in the telecommunication wavelength of 1.55 µm 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of As by Bi in the GaAs lattice produces a much larger reduction in the band gap (-60 to -80 meV/%Bi) [1,2] than alloying by In (-12 meV/%In) and Sn (-20 meV/%). Also, Bi is the heaviest nonradioactive element; therefore, it has a large spin orbit splitting, which is useful for spin-based semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%